“It was just my name!”: A CRT/CRF Analysis of International Female Graduate Students’ Perception and Experiences Regarding Their Ethnic Name - Wang, Peiwen; Gu, Xiaoyan; Morales, Amanda (Journal of International Students, 2022)
Although international female students accounted for 44% of the enrolled international students in the United States (U.S. Department of Homeland Security’s Student and Exchange Visitor Information System, 2020), their experiences regarding their ethnic name are relatively understudied in onomastic literature. This study considers the experiences of eight international female graduate students of Color who are studying at a Midwestern predominantly White university. Utilizing Critical Race Theory (CRT) and Critical Race Feminism (CRF) as the theoretical and analytical lenses, this qualitative phenomenological study collected data through semi-structured, in-depth interviews. We explore the meaning of ethnic names and their connection to participants’ multidimensional identities. Findings include experiences with microaggressions, discrimination, and racism among students in relation to their ethnic name, and point to underlying factors. Finally, implications are offered for students, faculty members, and administrators to build authentically inclusive and equitable learning communities more effectively.